An alternative water resource project for the state of Colorado: the Million - Green River Basin Water project: a comparative economics study and cost-benefit analysis of the Colorado River and Green River basins - Million, Aaron P., author; Hoag, Dana, advisor; Loomis, John, committee member; Frasier, Marshall, committee member; Grigg, Neil, committee member (Colorado State University. Libraries, 2015)
Water supplies are a limiting factor in the Western United States. Policy, social welfare, and economic interests all reflect the demands placed on this scarce resource. Projects to develop water are complex and reflect both historical and current institutional, environmental, and financial constraints. This study proposes a project from the Green River Basin for use in the State of Colorado. Water managers called this study the first new idea in water resources in 50 years. The cost-benefit analysis identifies limits, constraints and opportunities from the Green River Basin compared to the Colorado River basin. Economic welfare issues reflect water's expanding use and legal constraints. Not a public good exclusively and not a private right exclusively, the procurement of water, water rights, and development history is influenced by water's legal standing, public policy, and economic benefits. In the western United States, the Colorado River Compact influences the division and equitable use of waters in the Colorado River Basin System. Significant infrastructure is part of the landscape influenced by the Compact and the need to allocate water in a constrained system. Recent public project proposals failed to identify a potential water supply from the Green River. Environmental benefits, comparative costs, and financial opportunities may allow a new paradigm in the development of a major water project by the private sector. The historic return to private development of water projects reflects current policy changes and markets. The private sector may have significant advantages over public development and meet or exceed public welfare goals related to conservation, environmental benefits, protection of irrigated farmland, and supply procurement.
Keywords: flaming gorge; pipeline; water; green river; transbasin